Azerbaijan: NATO’s outpost on the Caspian Sea (Anti-bellum, 2021)
Azerbaijan: NATO’s outpost on the Caspian SeaRick Rozoff On June 17 the defense minister of Azerbaijan, Colonel General Zakir Hasanov, recently a “hero” of the Great Patriotic War…